Evaluasi Kurikulum Pembelajaran Desain Interior ITENAS Tahun Ajaran 2017 Berdasarkan Kinerja Lulusan di Dunia Profesional (Studi Kasus: Lulusan Desain Interior ITENAS Angkatan 2016-2018) - Ashri, Putri Nur; Wibisono, Andriyanto (Serat Rupa: Journal of Design, 2024)
Interior design education has a critical role in creating competent graduates, specifically in the scope of professional interior design, who answer the problems of community needs through quality design ideas. Educational institutions need to ensure that the learning curriculum implemented can produce competent graduates following learning outcomes. ITENAS Interior Design, as one of the best interior design educational institutions in Bandung, plays a significant role in creating competent graduates who improve the community's quality of life and the residential environment. This sequential explanatory research evaluates the ITENAS Interior Design learning curriculum by assessing the performance of graduates in the Interior Design profession based on the educational curriculum components implemented during the study using a comparative descriptive approach. Overall, the Interior Design learning curriculum for the 2017 Academic Year of ITENAS does not meet the 'excellent' or very effective. The research results revealed that [1] ID ITENAS graduates from the 2016-2018 class had the best assessment in terms of attitude (89%) and could be further improved in terms of stance and independence, [2] The graduates' knowledge was considered to be quite good (66%) though the limitations are apparent from the aspect of technical problems and material treatments. [3] Lack of experience with real problems and a short work period means that graduates still need regular guidance, resulting in General Skills and Specific Skills scores being in the lowest positions (55% and 53%).